Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1210/me.2010-0352
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Induces miR-132 and miR-212 to Regulate Cellular Morphology and Migration in Immortalized LβT2 Pituitary Gonadotrope Cells

Abstract: GnRH is central to the regulation of reproductive function. It acts on pituitary gonadotropes to stimulate LH and FSH synthesis and secretion. We had previously presented evidence for translational control of LHβ synthesis; therefore we investigated whether micro-RNAs might play a role in GnRH regulation in LβT2 cells. We show here that GnRH strongly induces the AK006051 gene transcript that encodes two micro-RNAs, miR-132 and miR-212, within the first intron. We show furthermore that the AK006051 promoter reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…Rac1 has been shown to directly bind mTOR and facilitate its activation and localization to plasma membrane microdomains (Saci et al, 2011). Previous work by Godoy et al suggests that GnRH activates Rho family members through microRNA regulation of p250RhoGAP to mediate cell morphology and migration in LβT2 cells (Godoy, Nishimura and Webster, 2011). Other work in heterologous HEK293 cells transfected with GnRHR reveals that GnRH-induced Rac1 activation is important for phosphorylation and recruitment of focal adhesion kinase (FAK) to focal adhesions (Davidson, Pawson, Millar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 has been shown to directly bind mTOR and facilitate its activation and localization to plasma membrane microdomains (Saci et al, 2011). Previous work by Godoy et al suggests that GnRH activates Rho family members through microRNA regulation of p250RhoGAP to mediate cell morphology and migration in LβT2 cells (Godoy, Nishimura and Webster, 2011). Other work in heterologous HEK293 cells transfected with GnRHR reveals that GnRH-induced Rac1 activation is important for phosphorylation and recruitment of focal adhesion kinase (FAK) to focal adhesions (Davidson, Pawson, Millar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In our in silico prediction, we observed that several miRNAs were assigned to gene ontology processes termed as ''GnRH signaling pathway'' (among others). Previous studies have proven the effect of miRNA in GnRH signaling and also the effect of GnRH signaling in miRNA expression patterns (55)(56)(57)(58). The potential gene targets related to this process included kinases and calcium and MAPK signaling pathways, which are involved in FSH and LH production, which in turn could be affecting proper timing for oocyte meiosis and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Egy másik tanulmány-ban az egér központi idegrendszerének különböző részeit vizsgálva sikerült agyalapimirigyre specifikus miRNS-eket azonosítani [22]. Amellett, hogy a miRNSeknek az emberben is fontos szerepük van a normál mirigy fejlődésében [19,23,24] és hormontermelésében [25][26][27][28][29][30][31], az elmúlt években egyre több humán vizsgálat támasztja alá azt is, hogy részt vehetnek az adenomák kialakulásában és növekedésében [32][33][34][35].…”
Section: Mirns-expressziós Eltérések Az Agyalapimirigy-daganatokbanunclassified